Selective production of diethyl maleate via oxidative cleavage of lignin aromatic unit - Cai, Z; Long, J; Li, Y; Ye, L; Yin, B; France, L; Dong, J; Zheng, L; He, H; Liu, S; Tsang, S; Li, X (Elsevier, 2019)
As a major component of biomass, lignin is regarded as an ideal renewable feedstock for the production of versatile chemicals. However, because of its wide structural diversity, currently reported chemical conversions of lignin hardly lead to high yields of specific products, which significantly limits the economic efficiency of biomass process. Here, we have designed a series of polyoxometalate ionic liquid (POM-IL) catalysts that combine the advantages of ionic liquid and polyoxometalate with the introduction of acidity, reduction-oxidation, and miscibility properties for lignin-selective depolymerization. The bulk chemical diethyl maleate is generated as a single product with an impressively high yield and selectivity through controlled oxidative cleavage of lignin aromatic ring, suggesting that lignin-selective oxidation would be a promising method for diethyl maleate production via a sustainable route.